Solar wind-magnetosphere-ionosphere coupling: Pi2 observations - Sinha, A.K.; Vohat, P.; Pathan, B.M. (My University, 2010)
There had been a number of studies using satellite and ground based observations on the interaction between the solar wind and the magnetosphere, which shows highly complex temporal and spatial interaction between the two. The magnetotail provides an important channel for the flow of energy from solar wind to the ionosphere and atmosphere. Solar wind drives reconnection under certain conditions on the dayside magnetopause, connecting the interplanetary and geomagnetic fields. As a result, the field lines are swept back to the magnetotail where magnetic energy is built up. This stored energy may be converted to plasma kinetic energy either in continuous mode or impulsive mode. In either case, this kinetic energy appears in the energization of the electrons and ions which stream along the magnetic field line in the plasma sheet boundary layer towards the Earth. This flow of energized charged particles results in the form of energy deposition in the high latitude ionosphere and high latitude atmosphere manifesting in terms of aurora. It has been shown from the results obtained from the analysis of ground based magnetic data that, the solar wind driven energy through the magnetotail makes global appearance in the night side of the Earth in the form of Pi2 pulsations. Compressional waves, following plasma sheet thinning due to reconnection, move Earthward and cause plasmasphere to oscillate at discrete frequencies. The present analysis reveals that Pi2 energy is having a global impact on the low latitude in transferring the energy and momentum from solar wind to ionosphere through tail region. During a geomagnetic quiet period (Kp= -3), the scrutiny of the magnetic records from a wide chain of magnetic observatories in the low and mid latitudes gave signatures of plasmaspheric cavity oscillations at dominant frequencies of 11.72 mHz and 23.44 mHz. It has been confirmed from various other parameters such as solar wind dynamic pressure, interplanetary magnetic field and AE-indices that the observed waves are Pi2 type pulsations and may be associated with substorm onset.
Keywords: Magnetotail; Pi2 pulsations; Plasmaspheric cavity; Solar wind; Interplanetary magnetic field